Video Visits: Patient Satisfaction and Quality of Virtual Medical Care - Mhiim, Saddia Cheema; Kumar, Sajeesh (International Journal For Research In Health Sciences And Nursing, 2016)
Electronic medical services via video visits has revolutionized the delivery of medical care by Physicians and medical staff alike. Its steady evolution and progression towards the future of healthcare has provided insight on how to better serve patients and community members seeking care. This study explores patient satisfaction and the quality of virtual medical care services provided by Physicians thru video visits as well as the impact of minimizing the spread of communicable diseases. Statistical data was gathered from a major U.S. healthcare company evaluating survey responses as well as feedback provided by member experience who visited with their respected providers via video visits. While the data captures survey response over a one year time frame, it provides insight towards positive future trends concerning video visits and how providers may use this information to improve services delivered to patients. This information may also serve valuable purpose for physicians in understanding technological advancements associated with the use of video visits, trends associated with cost effectiveness, marketability, competitors edge, patient satisfaction, and effective use of time as well as demonstrate its superiority to in person face to face patient visits with physicians.